Democracy, Constitutionalism, and Politics in Africa: Historical Contexts, Developments, and Dilemmas. - Formella, Collins Nkapnwo (Afrika Tanulmányok / Hungarian Journal of African Studies, 2021)
Edited by Eunice N. Sahle. Palgrave Macmillan, New York, 2017. p. 299. DOI 10.1057/978-1-137-55592-2